19th Century French Animal Protection, No Longer a Bête Curieuse: Review of Christophe Traïni, The Animal Rights Struggle: An Essay in Historical Sociology - Cherry, Elizabeth (Humanimalia, 2017)
Christophe Traïni. The Animal Rights Struggle: An Essay in Historical Sociology. Amsterdam: Amsterdam University Press, 2016. 206 pp. $99 (hc).